Structure de la végétation et potentiel de séquestration du carbone de la Réserve forestière de l’Université Peleforo Gon Coulibaly de Korhogo (nord de la Côte d’Ivoire) - Pagadjovongo Adama Silué; Dramane Soro; Adjoua Bénédicte Koffi; Koffi Appolinaire Yao (VertigO, 2023)
Carbon dioxide reduction by trees is an important ecosystem service for human well-being. It is often overlooked by beneficiaries, and rarely taken into account in studies. The aim of this study was to determine the carbon sequestration potential of the vegetation of the forest relic of the Peleforo Gon Coulibaly University in Korhogo (Northern Côte d'Ivoire). For the collection of dendrometric data, all individuals with a diameter at breast height (dbh) ≥ 5 cm were measured in 900 m² square plots (30 m x 30 m). The average density of woody plants was 788 plants/ha. The distribution by diameter classes of the woody plants revealed a predominance of small diameter individuals. The amount of biomass produced by the forest reserve was 219.92 t/ha corresponding to a sequestered carbon stock of 109.96 t/ha, and a CO2 equivalent of 403.18 t/ha. Individually, local species such as Adansonia digitata and Ceiba pentandra sequester the most CO2 in the reserve. The total amount of carbon sequestered was estimated at 16942.07 tonnes. This carbon stock potential shows the importance of the compensatory role of the forest reserve in the carbon dioxide emissions from anthropogenic activities in the Poro region.